2014
DOI: 10.3390/molecules19056822
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antibacterial Activity of Amino Acid and Dipeptide Prodrugs of IMB-070593, a Fluoroquinolone Candidate

Abstract: A series of amino acid and dipeptide prodrugs of IMB-070593, a fluoroquinolone candidate discovered in our lab, were synthesized and evaluated for their water solubility and then antibacterial activity. Our results reveal that four amino acid prodrugs 4a,b,e,f and two dipeptide prodrugs 4k,l have much greater solubility (>85 mg/mL) than IMB-070593 mesylate (22.5 mg/mL). Compounds 4a and 4k show good in vivo efficacy against MSSA 12-1 (p.o./i.v., 5.32-7.68 mg/kg) and S. pneumoniae12-10 (p.o., 18.39-23.13 mg/kg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
(18 reference statements)
0
13
0
Order By: Relevance
“…As reported, norfloxacin was used as a positive control in the pipeline publications, including norfloxacin derivatives synthesis. Norfloxacin MIC against Gram-positive is presented in Table 3 [ 1 , 23 , 24 , 26 , 28 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. In brief, norfloxacin inhibitory activity against a panel of Gram-positive bacteria regardless of the strain varied relatively.…”
Section: Fq’s Antibacterial Biological Activitymentioning
confidence: 99%
“…As reported, norfloxacin was used as a positive control in the pipeline publications, including norfloxacin derivatives synthesis. Norfloxacin MIC against Gram-positive is presented in Table 3 [ 1 , 23 , 24 , 26 , 28 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. In brief, norfloxacin inhibitory activity against a panel of Gram-positive bacteria regardless of the strain varied relatively.…”
Section: Fq’s Antibacterial Biological Activitymentioning
confidence: 99%
“…Based on that, various fluoroquinolones 12 (Fig. ) with different oximes at C‐7 position were screened for their antibacterial , antitumor , and anti‐TB activities by our group. The preliminary results indicated that the side chains at C‐7 position have great influence on their biological activities, and the anti‐TB SAR revealed that (1) piperidine > pyrrolidine > azetidine; (2) small –H was more favorable than large –Me at R 2 position, which may be attributed to the steric hindrance; (3) for the fluoroquinolone moieties, C‐OMe ≈ CH ≥ N. Among them, the oxime‐functionalized piperidinyl‐based fluoroquinolone IMB‐070593 displayed excellent antibacterial and anti‐TB activities as well as extremely low phototoxicity, hepatotoxicity, and cardiac toxicity .…”
Section: Quinolone‐based Derivativesmentioning
confidence: 99%
“…Quinolones with oxime‐functionalized azetidines, pyrrolidines, or piperidines have caused great interests since the discovery of the fourth generation FQs GMFX and its derivatives zabofloxacin as well as DW286, which exhibit excellent in vitro and in vivo activities against both Gram‐positive and Gram‐negative organisms including quinolone‐resistant pathogens and improved pharmacokinetic profiles . Some of them were found to have considerable activities against Gram‐negative bacteria, but few of them were superior to GMFX.…”
Section: Structure–activity Relationshipmentioning
confidence: 99%